The Eastern Democratic Republic of Congo Recurring Conflict: Whose Conflict Transformation Responsibility? - Sadiki Maeresera (UUM Press, 2018)
The recurring conflict in Eastern DRC has had devastating effects on civilians, mostly in Kivus. From the beginning of January 2002 till the end of May 2017, many conflict resolution efforts have been put together by regional and international communities. However, there has not been any sustainable mechanism to resolve the conflict. The situation regarding the security of Eastern Congo continues to be volatile. This paper seeks to identify the responsible party that would help mitigate the recurring conflict in Eastern Congo. Using the three distinct categories of actors in Conflict Transformation, the paper argues that the lack of coordination among these actors who constitutes the three Track levels have affected unity of purpose and the level of commitment as far as transforming the Eastern Congo Conflict. The divergent interests among the respective actors to outmaneuver one another when it comes to agenda setting regarding respective peace initiatives on conflict, could be the rationale behind the absence of a workable formula in transforming conflict in the Eastern DRC. The paper proffer strategic policy suggestions toward a workable Conflict Transformation mechanism that equitably addresses the root causes of the conflict and fairly incorporates the relevant stakeholders in an effort to find a sustainable solution.